MANGROVE ECOSYSTEM AND CLIMATE CHANGE MITIGATION: A LITERATURE REVIEW - Dian Nuraini Melati (Badan Pengkajian dan Penerapan Teknologi (BPPT), 2021)
Mangrove ecosystem has high productivity both ecologically and economically. Mangroveecosystems have the ability to store high carbon which is useful in supporting the reduction ofgreenhouse gas emissions. The results of previous studies have shown that mangroveecosystems are able to store carbon three to four times greater than terestrial forests. Most ofthe carbon are stored in the soil. Therefore, ecosystem mangroves have an important role tomitigate climate change. However, mangroves can be effective in supporting the mitigation ofcarbon dioxide emissions if mangrove deforestation rates are low. However, mangroves canstill contribute with great potential when conservation are maintained to increase future carbonstocks through restoration and prevent further emissions from deforestation. Existing data andprior research indicate that mangrove forests are threatened due to mangrove coveragereduction. This is caused by changes in land use. There are many conversions of mangrovesinto cultivation ponds, as well as conversions into agricultural land such as paddy fields andpastures, accompanied by an increase in demand for oil palm which causes land clearing. Inaddition, the population around the coastal area is increasing, resulting in the clearing ofmangrove land for infrastructure development such as road and port construction. In order toreduce the rate of mangrove deforestation, it is necessary to conserve and restore mangroves.By preserving mangrove forests, not only maintain carbon stocks for climate change mitigationbut also facilitate adaptation to climate change such as sea level rise.